Excitation-contraction coupling and excitation-transcription coupling in blood vessels: their possible interactions in hypertensive vascular remodeling - Misárková, E; Behuliak, M; Bencze, M; Zicha, J (Physiological research, 2016)
Vascular smooth muscle cells (VSMC) display considerable phenotype plasticity which can be studied in vivo on vascular remodeling which occurs during acute or chronic vascular injury. In differentiated cells, which represent contractile phenotype, there are characteristic rapid transient changes of intracellular Ca(2+) concentration ([Ca(2+)]i), while the resting cytosolic [Ca(2+)]i concentration is low. It is mainly caused by two components of the Ca(2+) signaling pathways: Ca(2+) entry via L-type voltage-dependent Ca(2+) channels and dynamic involvement of intracellular stores. Proliferative VSMC phenotype is characterized by long-lasting [Ca(2+)]i oscillations accompanied by sustained elevation of basal [Ca(2+)]i. During the switch from contractile to proliferative phenotype there is a general transition from voltage-dependent Ca(2+) entry to voltage-independent Ca(2+) entry into the cell. These changes are due to the altered gene expression which is dependent on specific transcription factors activated by various stimuli. It is an open question whether abnormal VSMC phenotype reported in rats with genetic hypertension (such as spontaneously hypertensive rats) might be partially caused by a shift from contractile to proliferative VSMC phenotype.
Keywords: vápníková signalizace; Animals; spřažení excitace a kontrakce; Excitation Contraction Coupling; hypertenze; cévy; Muscle, Smooth, Vascular; Transcription, Genetic; lidé; signální transdukce; Signal Transduction; remodelace cév; genetická transkripce; Hypertension; Calcium Signaling; svaly hladké cévní; Vascular Remodeling; Blood Vessels; zvířata; Humans